Let the nations be glad! : the supremacy of God in missions - Piper, John, 1946- (Grand Rapids, MI, Baker Academic, 2022)
"This 30th anniversary edition of John Piper's bestselling book shows that worship is the ultimate goal of the church and provides readers with a sound theological foundation for missions"--
Includes bibliographical references and indexes.
Keywords: Missions -- Theory; God (Christianity) -- Worship and love